The Drug-Resistance Mechanisms of Five Platinum-Based Antitumor Agents - Zhou, Jiabei; Kang, Yu; Chen, Lu; Wang, Hua; Liu, Junqing; Zeng, Su; Yu, Lushan (Frontiers in Pharmacology, 2020)
Platinum-based anticancer drugs, including cisplatin, carboplatin, oxaliplatin, nedaplatin, and lobaplatin, are heavily applied in chemotherapy regimens. However, the intrinsic or acquired resistance severely limit the clinical application of platinum-based treatment. The underlying mechanisms are incredibly complicated. Multiple transporters participate in the active transport of platinum-based antitumor agents, and the altered expression level, localization, or activity may severely decrease the cellular platinum accumulation. Detoxification components, which are commonly increasing in resistant tumor cells, can efficiently bind to platinum agents and prevent the formation of platinum–DNA adducts, but the adducts production is the determinant step for the cytotoxicity of platinum-based antitumor agents. Even if adequate adducts have formed, tumor cells still manage to survive through increased DNA repair processes or elevated apoptosis threshold. In addition, autophagy has a profound influence on platinum resistance. This review summarizes the critical participators of platinum resistance mechanisms mentioned above and highlights the most potential therapeutic targets or predicted markers. With a deeper understanding of the underlying resistance mechanisms, new solutions would be produced to extend the clinical application of platinum-based antitumor agents largely.